Diabetes in Pregnancy The Complete Guide to Management (Springer International Publishing, 2018)
This book is a comprehensive and easily accessible reference for physicians caring for pregnant women with diabetes. Covering patients with type 1, type 2, and gestational diabetes, this handbook offers guidance on the different methods of treatment necessary for each population. Chapters cover the entire scope of patient care, including: diagnosis, patient education, dietary recommendations, medications, management during labor, potential fetal complications, and postpartum management. Obstetricians, gynecologists, primary care physicians, and residents will use this text to quickly answer any question they have on diabetes and pregnancy.